Photonic eigenmodes and light propagation in periodic structures of chiral nanoparticles - A. Christofi; N. Stefanou; G. Gantzounis (Physical Review B, 2011)
We present a detailed analysis of the optical modes and light propagation in photonic crystals consisting of chiral spheres in a nonchiral isotropic medium, calculated by the full electrodynamic layer-multiple-scattering method. It is shown that resonant modes of the individual spheres give rise to narrow bands that hybridize with the extended bands of the appropriate symmetry associated with light propagation in an underlying effective chiral medium. The resulting photonic dispersion diagrams exhibit remarkable features, peculiar to a system that possesses time-reversal but not space-inversion symmetry, which are analyzed in terms of group theory. In particular, we reveal the occurrence of strong band bending away from the Bragg points with consequent negative-slope dispersion inside the first Brillouin zone, slow-photon bands, and frequency gaps. The calculated band structure is discussed in conjunction with relevant reflection diagrams, providing a consistent interpretation of the underlying physics.